The Impact of Shopee E-Commerce and Instagram Based Social Media Marketing on the Growth of Food Micro, Small, and Medium Enterprises (MSMEs) in Depok City - Sari, Nurul Rahma; Islami, Agnemas Yusoep; Dewi, Nur Fitri (International Publisher (YAPENBI), 2026)
This study aims to analyze the influence of Shopee e-commerce and Instagram social media marketing on the growth of food MSMEs (Micro, Small, and Medium Enterprises) in Depok City, both partially and simultaneously. The researcher employed a quantitative research approach using a questionnaire as the research instrument, measured with a Likert scale and processed into quantitative data. The sampling method used in this study is Non-Probability Sampling with a purposive sampling technique, adjusted to the criteria of respondents who are food MSME actors in Depok utilizing Shopee and Instagram in their marketing activities. The data analysis process was conducted using SPSS version 27. The results indicate that both Shopee e-commerce (X1) and Instagram social media marketing (X2) have a significant and positive influence, both partially and simultaneously, on the growth of food MSMEs (Y) in Depok City. The coefficient of determination results show that the two independent variables Shopee E-Commerce and Instagram Social Media Marketing contribute 61.9% to the growth of food MSMEs. Meanwhile, the remaining 38.1% is influenced by other variables not discussed in this study, as indicated by an R Square value of 0.619.This study aims to analyze the influence of Shopee e-commerce and Instagram social.